2020
DOI: 10.32800/abc.2021.44.0067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevation gradient and aspect on butterfly diversity on Galičica Mountain in the Republic of Macedonia (south–eastern Europe)

Abstract: The patterns of butterfly diversity and community changes in relation to elevation are an interesting and well–covered topic in ecology, but the effects of aspect have rarely been evaluated. Here we studied the changes in butterfly species richness and communities along the elevation gradient and aspect of Galičica Mountain. As expected, species richness changed with altitude, showing a bimodal pattern with two peaks and a declining trend towards higher altitude. Changes were well–correlated with the area in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…In general, the number of specimens and species decreases as the altitudinal gradient increases (Mihoci et al, 2011). The results of diversity analysis according to the altitudinal changes were consistent with findings from other studies (Meléndez-Jaramillo et al, 2019;Habel et al, 2019;Topp et al, 2019;Popović et al, 2021;Kaltsas et al, 2018). Several studies have indicated that altitude is a crucial factor that affects climate patterns and the variation in plant species, which in turn have a significant influence on the distribution of butterfly species (Eyre et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In general, the number of specimens and species decreases as the altitudinal gradient increases (Mihoci et al, 2011). The results of diversity analysis according to the altitudinal changes were consistent with findings from other studies (Meléndez-Jaramillo et al, 2019;Habel et al, 2019;Topp et al, 2019;Popović et al, 2021;Kaltsas et al, 2018). Several studies have indicated that altitude is a crucial factor that affects climate patterns and the variation in plant species, which in turn have a significant influence on the distribution of butterfly species (Eyre et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Koritnik in the Republic of Kosovo demonstrate a rich butterfly fauna, with 131 species recorded, accounting for 75.28% of the total number of species in Kosovo. This number of 131 recorded species makes up 75.2% of 174 species recorded so far in Kosovo (Rebel, 1913;Rebel & Zerny 1931;Jakšić & Živić, 1998;Zhushi-Etemi et al, 2016, 2017a, 2017bKoren et al, 2021;Kabashi-Kastrati et al, 2022) (Krpač et al, 2011;Popović et al, 2021), and 167 species in Stara Planina in Serbia (Popović et al, 2013;Langourov, 2019). Considering 496 butterfly species recorded in Europe (Wiemers et al, 2018), the 131 species recorded in our survey represent 26.14% of European butterfly fauna.…”
Section: Discussionmentioning
confidence: 97%
“…Faifa, we have not expected such a pronounced altitudinal segregation of butterflies (Figure 4). Both a reduction of butterfly richness with altitude and a midelevation peak of richness, commonly observed in similar studies (Gallou et al 2017;Popović et al 2021), were evident on Mt. Faifa.…”
Section: Discussionsupporting
confidence: 77%
“…Overall, butterflies and their diversity are stronger at lower elevations and gradually decline at higher elevations because floristic diversity declines when they rely on to survive and reproduce. Butterfly richness and abundance decline with altitudes, and species composition changes along the altitudes [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%